Complete Blood Checkup using Image Processing - Guda Sai Manisha, Rohith. R. Bharadwaj, Nayani Lathasree, Chinnareddyvari Nikhil, Rashmi. K (International Journal of Advanced Science and Technology, 2020)
In this paper, we are proposing a method in which we incorporate the image analysis & classification algorithm with the manual counting method of blood cell which gives results comparable with the very sophisticated automated blood cell counters. Image acquiring is done with the help of manual blood counting slide, USB compatible microscope and store it in the system or a computer for further processing. The stored image is processed through software to enhance the quality of the image for accurate output data, which we compare with our known values and giveanefficiencyoftheacquiredoutput.WehaveusedMATLABandScilabastheimageprocessingsoftware.